Literature Review: Pengaruh GCG, Ukuran Perusahaan, Dan Leverage Terhadap Kualitas Laba di Perusahaan Manufaktur - Izza Ersa Hakim; Dheo Rimbano; Yuli Nurhayati; Muhammad Syabihi; Bilqis Rihadatul Aisy; Mirandha Maulidia; Cassandra Qarhoma (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to examine the influence of Good Corporate Governance (GCG), firm size, and leverage on earnings quality in manufacturing companies in Indonesia. Using the Systematic Literature Review (SLR) method on 30 relevant journals, the research finds that GCG consistently has a positive impact on earnings quality through mechanisms such as institutional ownership and audit committees, which enhance the transparency and accountability of financial reports. Firm size also contributes positively, as larger companies tend to have better resources and oversight, although external pressures may affect the results. Conversely, leverage negatively influences earnings quality, as financial pressures often lead to earnings manipulation practices. This study provides comprehensive insights into how these three variables interact and influence earnings quality, while also offering recommendations for improving corporate governance practices and sound financial management in the manufacturing sector.